Bacteremia due to Parabacteroides distasonis: Experience with 4 cases. (August 2022) - Cobo, Fernando; Pérez-Carrasco, Virginia; Franco-Acosta, Ana; García-Salcedo, José A.; Navarro-Marí, José María
Abstract: Objective: To report a series of four uncommon cases of bacteremia due to Parabacteroides distasonis . Methods: We have analyzed the epidemiological characteristics, clinical features, diagnostic methods, treatment and outcome of these patients. Results: Two sets of blood cultures of each patient yielded a pure culture of an anaerobic microorganism identified as P. distasonis by MALDI-TOF MS, and confirmed by 16S rRNA gene sequencing . All patients were male and they had risk factors for anaerobic bacteremia. All isolates were susceptible to metronidazole and the outcome was successful in three patients. Conclusions: Bloodstream infections due to P. distasonis are still rare. MALDI-TOF MS appear to be an excellent tool for the correct identification. Highlights: Parabacteroides distasonis has been rarely associated with bacteremia. All patients had risk factors for anaerobic bacteremia. MALDI-TOF MS provided a correct species identification. All isolates showed resistance to benzylpenicillin.